Women and stroke: how much do women and men differ? : a review – diagnostics, clinical differences, therapy and outcome - Vuković, Vlasta (Array, 2009)
Abstract: In this article, the authors have gathered data from epidemiological, observational, case-control and cohort studies to evaluate the differences between men and women in terms of ischemic events, mainly stroke. The authors are highlighting the differences that exist between men and women and play a role in terms of social diversities, and the pathophysiological differences that may be responsible at least in part for ischemic events. Studies show that male stroke patients are more likely to have a history of ischemic heart disease, smoking and alcohol consumption, whereas female stroke patients suffer from ischemic events at an older age, are more likely to have hypertension and atrial fibrillation. Women are more likely to arrive to an emergency room in a comatose state, with paralysis, aphasia, swallowing problems and urinary incontinence, which all indicates a more severe stroke. Also, women suffer from a higher level of disability than men, even though their survival rates are the same. Even though clear guidelines for the treatment of stroke exist, there are still differences in both diagnostic procedures and discharge destination between male and female patients